2013
DOI: 10.1002/jnr.23301
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of TDP43 and FUS/TLS protein expressions in the preconditioned hippocampus following repeated transient ischemia

Abstract: The 43-kDa transactivation response DNA binding protein (TDP43), fused in sarcoma/translocated in liposarcoma (FUS/TLS), heat shock protein 70 (HSP70), and β-amyloid (Aβ) are induced and involved in cerebral ischemia, amyotrophic lateral sclerosis (ALS), and Alzheimer's disease (AD), but their relationships in ischemic tolerance have never been examined, although they could be involved in endogenous neuroprotection under ischemic preconditioning. In the present study, Mongolian gerbils were subjected to one or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…TARDBP, also known as TDP-43, has been identified as a major constituent of proteinaceous inclusions characteristic of most forms of amyotrophic lateral sclerosis and frontotemporal lobar degeneration (22) . The 43-kDa transactivation response DNA binding protein (TDP43), FUS/TLS, heat shock protein 70, and β-amyloid have been reported to be induced and involved in cerebral ischemia, amyotrophic lateral sclerosis, and Alzheimer's disease (23) . However, their involvements in ischemic tolerance have never been examined, although they could be involved in endogenous neuroprotection under ischemic preconditioning (23) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TARDBP, also known as TDP-43, has been identified as a major constituent of proteinaceous inclusions characteristic of most forms of amyotrophic lateral sclerosis and frontotemporal lobar degeneration (22) . The 43-kDa transactivation response DNA binding protein (TDP43), FUS/TLS, heat shock protein 70, and β-amyloid have been reported to be induced and involved in cerebral ischemia, amyotrophic lateral sclerosis, and Alzheimer's disease (23) . However, their involvements in ischemic tolerance have never been examined, although they could be involved in endogenous neuroprotection under ischemic preconditioning (23) .…”
Section: Resultsmentioning
confidence: 99%
“…The 43-kDa transactivation response DNA binding protein (TDP43), FUS/TLS, heat shock protein 70, and β-amyloid have been reported to be induced and involved in cerebral ischemia, amyotrophic lateral sclerosis, and Alzheimer's disease (23) . However, their involvements in ischemic tolerance have never been examined, although they could be involved in endogenous neuroprotection under ischemic preconditioning (23) .…”
Section: Resultsmentioning
confidence: 99%
“… 10 Dysregulation of TAR-DNA binding protein 43 (TDP43) confers to various disorders such as amyotrophic lateral sclerosis, brain ischemia, and Alzheimer’s disease. 11 Also, dysregulation of TDP43 contributes to the progression of neuroblastoma and breast cancer. 12 However, the profiling of TDP43 in glioma remains incompletely delineated.…”
Section: Introductionmentioning
confidence: 99%
“…Their work identified 43 kDa transactivation response DNA-binding protein (TDP43), fused in sarcoma/translocated in liposarcoma (FUS/TLS), and heat shock protein 70 kDa (HSP70) as potential mRNA targets. This group demonstrated the neuroprotective role of these proteins in a previous investigation [55]. Other corroborative work has shown that miR-132, which targets FUS/TLS, increased and peaked at post-injury day 1, but was subsequently downregulated from 7 days to 6 months after ischemia [54].…”
Section: Ischemic Preconditioningmentioning
confidence: 68%